The Effect of Transformational Leadership and Organizational Culture on Organizational Performance with Employee Engagement Mediation - Syafri, Muhammad; Sono, Mohammad Gifari (West Science Business and Management, 2025)
This study investigates the influence of transformational leadership and organizational culture on organizational performance with employee engagement as a mediating variable. Using a quantitative approach, data were collected from 190 respondents through a structured questionnaire employing a five-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that organizational culture has the strongest positive and significant effect on organizational performance, followed by transformational leadership. Furthermore, organizational performance significantly influences employee engagement, highlighting its role as a driver of employee commitment and motivation. The R² values demonstrate that the model explains 84.0% of the variance in organizational performance and 62.5% of the variance in employee engagement, suggesting strong explanatory power. These findings emphasize the importance of embedding strong cultural values and transformational leadership behaviors to enhance organizational performance and foster employee engagement.